Cotton water requirements - de Azavedo, Pedro Vieira; Rao, T. V. Ramana; Neto, Malaquias da Silva Amorin; Pereira, José Renato Cortez; Sobrinho, José Espínola; Maciel, Girlene Figueiredo (Pesquisa Agropecuaria Brasileira, 1993)
A field experiment with irrigated cotton was conducted at Sousa, PB, Brazil, in the period from August to December, 1990. Its objective was to measure daily maximum crop evapotranspiration (ETm) and reference potential evapotranspiration (ETo), estimated by climatological methods, in order to establish the seasonal behaviour of the crop coefficient (Kc = ETm/ETo). A 0.7 ha plot was planted in a 1.00 m row and 0.20 m between plant spacing. Irrigation was made by furrows. The meteorological parameters were daily observed above the canopy. The maximum daily water consumption occurred in the tenth week (ETm = 6.4 mm/day) and the seasonal total water consumption of 440.0 mm. ETo showed a tendency for overestimating ETm in the phases of germination and vegetative growth and for underestimating it in the period of full crop development. The methods of estimation of ETo showed statistically no significant differences, with Penman's method showing the lowest difference in relation to those values suggested by FAO. Kc values showed good agreement with those suggested by FAO. A Kc characteristic curve was established for the crop growing season. The crop showed a low transpiration rate even in excellent soil water conditions.